PROVISION OF COLLECTION OF INFORMATION FOR THE THREE-DIMENSIONED: Array - Shypulin, V.; Nesterenko, S.; Holovachov, V.; Kasyanov, V. (Municipal economy of cities. Series: «Economy science», 2019)
The purpose of the article is to review the existing methods of gathering source information when constructing three-dimensional models of real estate objects in the aspect of multi-purpose cadastre. The role of international regulatory support in the cadastral system of Ukraine is revealed. The peculiarities of information gathering by means of various topographic-geodetic surveying tools for informational support of three-dimensional modeling of real estate objects are determined. Previous studies of scientists in the field of 3D real estate modeling have been analyzed, compared with leading 3D real estate modeling systems. Land management systems deal with information about land (real estate). One of the properties of a land plot is the location of its boundaries and how they relate to neighboring objects. Each land plot is subject to cadastral surveying. And if we are talking about a multi-purpose cadastre system, then we have to consider a three-dimensional cadastre, which is about registering the rights of not only a certain part of the territory, but also a certain space (volume) to which the right of ownership extends. Currently, the cadastre of cadastre objects is implemented in two-dimensional form in Ukraine. That is, to determine the position of the land plots is fixed by entering in the cadastre of values ​​of rectangular coordinates (X, B) of the points of rotation of the boundaries of the land plot. Which, in turn, ensures the exact anchorage of the land plots in kind (on the ground), the account of their areas, the quantitative and qualitative characteristics of the plots, the configuration and position relative to the adjacent land plots. In order to ensure the operation of a three-dimensional cadastre, as opposed to a two-dimensional one, information about the third coordinate, that is, the height of the object, is a prerequisite. In the three-dimensional GIS system, in addition to the X, B coordinates, the elevation coordinate (H) must be taken into account. Providing this coordinate information requires additional resources to collect, process, save, and subsequently use it in GIS. There are three types of cadastre: full 3D cadastre, hybrid and 3D tags in existing 2D cadastre. As a prerequisite for the creation of a single information space is the requirement of spatial and temporal binding of information on all objects of real estate and land of the city, there is a problem of providing any land-planning projects with topographic-geodetic materials, which has a sharp character and requires certain and sequential actions to form the basis for further development. In this article, we will look at existing methods for collecting source information, with its subsequent ability to use in 3D cadastre.